Different Antioxidants Modulate Several Steps Of Ferroptosis Associated With Neurodegeneration - Conde, Melisa Ailén (2024)
A recently described form of regulated cell death named ferroptosis has been associated with several neurodegenerative processes. The most prominent mechanisms related to ferroptosis are iron accumulation, lipid peroxidation, and mitochondrial disorganization associated with glutathione (GSH) depletion. We aimed to investigate the effect of well-known antioxidants in the above-described mechanisms related to neuronal death by ferroptosis. To this end, we used the pesticide maneb which has been described as a pro-ferroptotic stimulus and whose exposure is associated with Parkinsonism. We found that maneb can trigger dopaminergic neuronal death in a time- and concentration-dependent manner (p<0.01). Neuronal death was accompanied by diminished GSH content (p<0.05), and the typical mitochondrial pattern of ferroptosis (p<0.001). Moreover, maneb treatment was able to increase neuronal alpha-synuclein (aSyn) expression (p<0.05). Using this neurodegenerative framework, we evaluated two different antioxidants: N-acetylcysteine (NAC), a GSH precursor, and ferrostatin-1, a radical-trapping agent. We found that NAC was able to revert aSyn overexpression in maneb-exposed neurons (p<0.05) and that ferrostatin-1 was able to re-establish mitochondrial architecture to that of control neurons (p<0.001). Intriguingly, luteolin, a flavonoid that acts as a free radical scavenger, increased cell death in neurons exposed to maneb (p<0.05). This later could be explained by the inhibitory effect of lipoxygenases exerted by luteolin. Our results show that antioxidants with different mechanisms of action target several steps of ferroptosis, and could be the starting point for further studies aimed at preventing neuronal death by this form of regulated cell death